La segregazione etnico-religiosa nel sistema educativo in Irlanda del Nord (Stato, Chiese e pluralismo confessionale, 2023)
La segregazione etnico-religiosa nel sistema educativo in Irlanda del Nord *Ethnic-religious segregation in the education system of Northern IrelandABSTRACT: After many years of conflict, Northern Ireland still appears today as a deeply divided society that bears the marks of centuries of ethnic hostility with a strong religious connotation. The context in which, more than any other, the segregationist tension between the two communities, Protestant and Catholic, is still clearly perceivable is the education system, which is characterized by a significant separation of students according to their religious affiliation. The paper aims at reconstructing the origins and outlining the focal points of such an education system, which was recently brought to the attention of the Northern Ireland Supreme Court, with reference to discrimination against students belonging to other religions or beliefs.SOMMARIO: 1. Premessa - 2. Le origini del conflitto politico-religioso - 3. Le persistenti difficoltà politiche e le ricadute sui rapporti interconfessionali - 4. La segregazione scolastica - 5. Profili di discriminazione religiosa nell’accesso alla scuola - 6. La discriminazione nell’insegnamento della religione: la recente pronuncia della High Court of Justice of Northern Ireland - 7. Conclusioni.